2017
DOI: 10.1007/s12613-017-1520-4
|View full text |Cite
|
Sign up to set email alerts
|

Solid FeS lubricant: a possible alternative to MoS2 for Cu–Fe-based friction materials

Abstract: Molybdenum disulfide (MoS 2 ) is one of the most commonly used solid lubricants for Cu-Fe-based friction materials. Nevertheless, MoS 2 reacts with metal matrices to produce metal sulfides (e.g., FeS) and Mo during sintering, and the lubricity of the composite may be related to the generation of FeS. Herein, the use of FeS as an alternative to MoS 2 for producing Cu-Fe-based friction materials was investigated. According to the reaction principle of thermodynamics, two composites-one with MoS 2 (Fe-Cu-MoS 2 sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…NAMO exhibited moderately poor resistance than others. The solid polarizing effect on the sulfur atom is shown by the small electropositive molybdenum present in the MoS 2 lattice layer (Peng et al , 2017). These electropositive poles result in excellent adhesive properties with the metal substrates.…”
Section: Resultsmentioning
confidence: 99%
“…NAMO exhibited moderately poor resistance than others. The solid polarizing effect on the sulfur atom is shown by the small electropositive molybdenum present in the MoS 2 lattice layer (Peng et al , 2017). These electropositive poles result in excellent adhesive properties with the metal substrates.…”
Section: Resultsmentioning
confidence: 99%
“…† This phenomenon accounted for the corrosion effect of MoS 2 , which is not conducive to the growth of Cu Nps. 50 In contrast with MoS 2 , PDA could provide the growth sites for Cu Nps and prevent the surface corrosion of MoS 2 . The Bragg diffraction pattern of Cu Nps was obtained by Fourier transform using the software Digital Micrograph, as shown in Fig.…”
Section: Biomaterials Science Papermentioning
confidence: 99%
“…Above all, the solid solution strengthening matrix materials can be formed through adding alloying elements such as Zn Ni, Sn and Fe; meanwhile, the mechanical properties of matrix materials can be improved by surface plating (Varol and Canakci, 2015; Senthil Kumar et al , 2013; Zou et al , 2018; Radhika et al , 2018; Zhang et al , 2016). It is effective to improve the interface adhesion, mechanical properties and tribological properties by adding MoS 2 into Cu-Fe, Cu-Sn alloy or copper-plated alloy (Varol and Canakci, 2015; Peng et al , 2017; Fu and Wang, 2010). It was found that the high-temperature tribological properties of the composites can be improved by the addition of an appropriate amount of MoS 2 at high temperatures.…”
Section: Introductionmentioning
confidence: 99%